KAJIAN DURABILITAS DAN PENUAAN ASPHALT CONCRETE-WEARING COURSE (AC-WC) ASBUTON PRACAMPUR TERHADAP VARIASI LAMA RENDAMAN - Attamimi, Mohamad Faldi; Achmad, Fadly; Desei, Frice L. (Composite Journal, 2021)
The fundamental problem in roads construction is the road damage that occurs before the road’s designted time is reached. Causes of such a damage consist of weather, water, temperature, or the reduction in the quality of pavement layers due the aging process. The manufacture of test object for Short-Term Oven Aging (STOA) was carried out by heating the test object in loose condition with 135°C of temperature for 4 hours before compaction, while the manufacture of test piece for Long-Term Oven Aging (LTOA) was carried out by heating the test object for 2 days in 85°C temperature after the specimen was compacted. The durability parameters of the AC-WC mixture was observed from Residual Streght Index (RSI), First Durability Index (FDI), and Second Durability Index (SDI). Based on the findings of Pre-Blended Buton Asphalt AC-WC mixture produced 6,0% of Optimum Bitumen Content (OBC). The RSI of the test object in normal, STOA, and LTOA obtained 97,11%, 94,82%, and 95,77% respectively. Furthermore, the FDI of the test object in normal, STOA, and LTOA obtained r value of 0,42%, 0,74%, and 0,60% respectively. Meanwhile, the SDI of the test in normal, STOA, and LTOA obtained a value of 4,87%, 9,75%, and 7,73% respectively. In addition, the Sa of the test object in normal, STOA, and LTOA in 96 hours of soaking were 95,13%, 90,25%, and 92,27% respectively. All in all, the finding showed that the AC-WC mixture with Pre-Blended Buton Asphalt in normal condition attained 72 hours of durability, while for the test specimen which is subjected to aging (STOA and LTOA) attained 48 hours of durability.